Creative Accounting: Apakah Suatu Tindakan Ilegal? - MF. Arrozi Adhikara (AKRUAL: JURNAL AKUNTANSI, 2011)
AbstractThis paper aims to explore the environment and the implementation of creative accounting events related to the context of ethical behavior and find solutions and ways to deal with matters creative accounting. Exploration carried out related to the definition of creative accounting, creative accounting in nature, ethics, reason for doing creative accounting practices, process behavior in creative accounting, as well as some summary results of empirical research about the events of creative accounting. Recent findings in this paper is to provide solutions and ways to prevent and solve problems in creative accounting accounting practices.